(untitled) (Vietnam Journal of Community Medicine, 2025)
Background: Accurate and culturally appropriate assessment of activities of daily living is essential for effective rehabilitation planning in stroke survivors. The VnRAs 2.0 is a 20-item instrument designed to evaluate both basic and instrumental activities of daily living in Vietnamese adults. Objective: To assess the internal consistency, test-retest reliability, and convergent validity of VnRAs 2.0 in stroke patients. Methods: A cross-sectional study was conducted on 53 subacute and chronic stroke patients at Hue Rehabilitation Hospital from March to May 2025. Each participant was assessed twice with the VnRAs 2.0, 5-7 days apart. Convergent validity was examined through correlations with the Barthel index and the Lawton IADL scale. Statistical analyses included Cronbach’s alpha, ICC, and Spearman’s correlation. Results: The VnRAs 2.0 demonstrated excellent internal consistency (Cronbach’s alpha = 0.965) and outstanding test-retest reliability (ICC = 0.99). Strong correlations were observed with the Barthel index (r = 0.907) and the Lawton IADL scale (r = 0.944). Notably, the ceiling effect of VnRAs 2.0 was lower (3.8%) compared to the Barthel index (17%). Conclusion: VnRAs 2.0 is a reliable, valid, and culturally relevant instrument for assessing daily living function in post-stroke Vietnamese patients. Its integration into both clinical practice and community-based rehabilitation is strongly recommended.